Risk factors and diagnosis of iatrogenic damage of periodontal structures and roots during orthodontic Mini-Implants implantation procedures - a systematic literature review - Nieścior, Hubert; Sereda, Dominika; Metelska, Aleksandra; Metelski, Jakub (Journal of Education, Health and Sport, 2022)
Introduction and purpose In recent years, Mini-Implants (MI) have gained popularity and new complications have emerged with them. The article assesses the current reports on the scale of the problem, factors and diagnostic possibilities related to iatrogenic injuries of periodontal tissues and roots. Description of the state of knowledge The incidence of complications was estimated to be 13.5%. Complications are more common in the mandible and are estimated at 20-27.1%. Periodontal and root damage are an important risk factor for treatment failure. The fact that the implant does not interfere with the alveolus structure gives the treatment effectiveness in 90%, and the contact with the alveolar “lamina dura” is 62.5%. Interference with the root structure is successful in only 31.2%. Risk factors for failure include: young age, poor hygiene, smoking, area of mandibular molars, contact with the root, thickness of the bone and lack of experience. The implant between the roots is a risk of root trauma, as the location close to the tooth cemento-enamel junction, no preparation for surgery, not using surgical templates, strenuous implantation or implant migration under the influence of orthodontic forces. Radiographs are the gold standard in the diagnosis of complications, but they do not allow for a full assessment of the three-dimensional structures of the implant. A promising method is the evaluation of the torque as the implant is placed in its final location. The patient’s subjective feelings are questionable in diagnosis and require further research. Summary There are many complications in using MI and the most important of these is damage to the structures of the periodontium and the tooth root. Despite the low failure rate, failure should be prevented by pre-operative evaluation, in-operative monitoring, and post-operative diagnostics.